Acquiring vulnerability indicators to geo-hydrological hazards: An example of mobile phone-based data collection. (March 2021) - Salvati, Paola; Ardizzone, Francesca; Cardinali, Mauro; Fiorucci, Federica; Fugnoli, Federico; Guzzetti, Fausto; Marchesini, Ivan; Rinaldi, Gianluca; Rossi, Mauro; Santangelo, Michele; Vujica, Ivan
Abstract: Geo-hydrological risk reduction is a key issue for local governments in Italy. In this context, a collaboration was undertaken between multiple actors in the La Spezia municipality aimed at: (i) monitoring building characteristics, using specific and valuable indicators, and (ii) increasing the knowledge of geo-hydrological hazards across residents and local land planners (iii) implementing local emergency civil protection plan. An extensive mobile data collection was carried out through apps specifically developed for Android and IOS mobile devices. The digital forms were differentiated on the basis of the potential hazard: one of 46 fields and one of 125 fields designed for buildings respectively located in flood prone areas and in medium to very high landslide susceptibility areas. The digital version of the forms was designed using the Open Data Kit (ODK) and GISCloud client-server approach. All the collected data, including geospatial locations and images, were automatically sent to a central server, stored and organized in a database. Geospatial data-analysis and maps resulted useful in evaluating possible impacts to exposed buildings to potential geo-hydrological processes. The proposed public participation method for data-gathering increased the knowledge across residents providing a better understanding of the urban systems, of the buildings condition and their relation respect to the geo-hydrological risk. The method can be considered as part of the decision support systems for civil protection purposes to better planning geo-hydrological mitigation measures. The application of mobile technology for data collection can be effectively used when local government resources are limited. Graphical abstract: Image 1 Highlights: The proposed technology allows the collection of several building characteristics to be used as vulnerability indicators. The designed survey-forms are made available and accessible through a dedicated link. The designed mobile application can be effective technology when local government resources are limited. The proposed public participation method increases the knowledge across residents of geo-hydrological risks. The outcomes constitute non-structural mitigation measures to manage geo-hydrological risk in both urban and rural context.